Development of SAVI Model Speaking Skills Textbook Introduction to Surabaya Typical Food for BIPA 2 Learners - Artadiyanti, Ni Made Novi; Suyatno; Yuniseffendri (International Humanity Advance, Business & Sciences, 2024)
This research aims to develop a speaking skills textbook based on the Somatic, Auditory, Visual, and Intellectual (SAVI) model with introduction materials for Surabaya typical foods for Indonesian learners for Foreign Speakers (BIPA) level 2. The development of this textbook is based on the needs of learners who need a contextual and interactive learning approach to improve speaking skills in authentic communicative situations. The research method used is the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The results of the study show that this textbook is effective and interesting for BIPA learners. The validation of material experts and media experts showed the category of "very decent" with scores of 92% and 90%, respectively. Product trials in small and large groups also showed a significant improvement in learners' speaking skills, based on the results of the pre-test and post-test with an average increase of 35%. This textbook is designed to support learners in getting to know Indonesian culture, especially Surabaya's culinary specialties, through learning activities that involve movement, hearing, visual observation, and intellectual analysis. Thus, this textbook can be one of the innovative and relevant learning media for BIPA learners, as well as contributing to introducing Indonesian local culture to the international world. This study recommends the use of the SAVI model for other learning materials to create a more contextual and meaningful learning experience.